State Control and Commercial Influence in Provisioning Constantinople - Hüseyin Erkan Bedirhanoğlu (Yüzüncü Yıl Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)

(untitled)
This article aims to analyze the provisioning system of Constantinople from the late eleventh century to the city's fall. It traces the evolution of Byzantine economic structures, focusing on the transition from state-controlled supply under the Roman model to a more decentralized system influenced by foreign merchants, particularly Italians. The paper explores the demographic fluctuations of Constantinople, highlighting population growth during the Komnenian Period and the challenges posed by territorial losses. It examines the crucial role of foreign merchants, changes in guild dynamics, and the shifting balance between state intervention and commercial activity in supplying the imperial capital. Drawing on legal texts like the Theodosian Code and contemporary accounts, it reveals a gradual loosening of state control over provisioning, particularly after the loss of Egypt in the seventh century. Through this analysis, the article sheds light on the complex interplay between state authority, economic structures, and external factors in sustaining the food supply of Constantinople amidst geopolitical upheavals and demographic changes.